Impacts of Temperature-Induced Change of Formulation Buffers on the Stability of Proteins in Solution - Jeluk, Aimée (2025)
Therapeutic proteins are most commonly formulated as liquid dosage forms. Buffers are fundamental components of liquid protein formulations incorporated with the purpose to maintain protein stability on changes, particularly in the formulation pH, arising from processing or storage. However, the properties of a buffering system, its pH, ionic strength and composition, are dependent on environment temperature and pressure. Consequently, the buffer per se can be the source of pH variations in liquid protein formulations exposed to temperature changes (temperature excursions) and in that way affect stability of proteins in solution. The aim of this thesis was to assess the effect of temperature-induced pH changes in different buffers on the conformational and colloidal stability of proteins in solution. It further considered if buffers can be designed such to increase stability of proteins in solution on potential changes in temperature.